Taxonomic and nomenclatural reassessment of the Iberian Peninsula’s nomina obscura, Scolopendra viridipes Dufour, 1820 and S. chlorotes L. Koch in Rosenhauer, 1856 (Chilopoda, Scolopendromorpha, Scolopendridae) - Carles Doménech (ZooKeys, 2024)
The taxonomic identities of the two largely neglected Scolopendra Linnaeus, 1758 species from continental Spain, S. viridipes Dufour, 1820 and S. chlorotes L. Koch in Rosenhauer, 1856, are examined in this paper. After efforts in locating both species’ type series in eight European institutions, the specimens are considered to be lost. Consequently, the identifications of both taxa were approximated by collating their descriptions with the morphology of all other sympatric Scolopendromorpha. Then, compatible topotypes for both species were collected, and among these a neotype for each taxon were selected and compared with the type series of their respective closest relatives. Finally, both S. viridipes and S. chlorotes are proposed to be conspecific with S. oraniensis Lucas, 1846. Therefore, the name S. viridipes is here established as (senior) syn. nov. and nomen oblitum of S. oraniensis, S. oraniensis is declared as nomen protectum, and S. chlorotes (junior) syn. nov. is reallocated to S. oraniensis. Moreover, the specimens making up the type series of S. oraniensis are also indicated and redescribed, the genitalia are illustrated for the first time, and its specific epithet is briefly reviewed, remaining unaltered in respect of its original spelling.